MARKETING COMMUNICATION ADAPTATION OF MSME IN THE DIGITAL ERA: RESPONDING TO CHANGES IN CONSUMER BEHAVIOR - Septina, Nina; Danil, Lilian; Satyarini, Ria (Review of Management and Entrepreneurship, 2019)
Technological development is one of the important factors in the process of purchasing decisions that affect consumer spending patterns. These changes are not just happening in Indonesia, but apply globally. The availability of high-speed internet connections, as well as the consumer's receipt of the presence of the power of social media and the number of online offerings increasingly attractive, support very well the growth of online business. This research aims to study the consumer behavior changes in the digital age. Data collection is done with a qualitative approach in the form of focus group discussion and depth interviews in several cities in Indonesia. Research results are applied as the basis for consideration for Small Medium Enterprises in conducting its marketing strategies adaptation in order to be sustainable in the digital age.